Country update: Indonesia - KHOIR, Safirotu (Institutional Knowledge at Singapore Management University, 2022)
Country updates from Singapore: - Institut Teknologi Bandung (Bandung Institute of Technology) - Universitas Airlangga (Airlangga University) - Universitas Gajah Mada (Gajah Mada University) - Universitas Indonesia (University of Indonesia)